To Hear Ourselves As Others Hear Us: Tape Recording As a Tool in Music Practicing & Teaching - Boyk, James (Saint Louis Mmb Music, 1996)
Following this easy approach, professional musicians, students, and teachers of all instruments will hear themselves more objectively, work more efficiently, and play more expressively. The book includes guides to choosing equipment and recording for commercial release. Rich in anecdotes and reflections on music-making, To Hear Ourselves As Others Hear Us is a reading delight.Show More Show Less